Classroom Interactions, Instructional Activities And Learning Affordances Of An Undergraduate Technical Writing Classroom: A Sociocultural Study - Cheah, Swi Ee (2014)

(untitled)
This thesis is the result of an academic venture to explore writing practices in the Malaysian higher education. The study assumes a sociocultural view and approaches writing practices as the teaching, learning, and doing of writing. Tesis ini dihasilkan menerusi satu usaha akademik untuk menerokai amalan menulis di institusi pengajian tinggi di Malaysia. Kajian ini berdasarkan pandangan sosiobudaya dan mengambil pendekatan terhadap amalan menulis sebagai pengajaran, pembelajaran dan perlakuan penulisan.